Hubungan Antara Faktor Konflik Pribadi Dengan kategori Skikizoprenia Pada Pasien Rawat Inap Di Bangsal - Sukatwo ,-; Margo Utomo (JURNAL LITBANG, 2005)
Bockground : Mental Healthy is condition may be to development physical,intelectual and emotional anyone individual by optimal hirmoniiing with development anyone the other in environment. Sktzofrenia is mental inteiefenceoften happened with incidence rate on the world